Articulation of Regional Community Interest Through DPD RI - I Gusti Bagus Suryawan (Sociological Jurisprudence Journal, 2018)
This paper examined the articulation of the interests of regional community through the authority of members of the Regional Representative Council (DPD) to see the extent of the functions and authorities of people representative officials in realizing the public interest of the regional people. This paper utilized conceptual approach and statutory approach to the law because of its normative type in nature. Therefore, the required data were in form of articles of the law regulating the authority of members of the Regional Representatives Council (DPD) as well as the interests of the society in the region. In addition, data from bibliography were also collected, such as results of scientific studies relevant to the object of study in the present study to compare theories leading to meet conclusions to be drawn. The results show that the articulation of the interests of regional community within the scope of the authority of the DPD is still very limited because it is at the theoretical level, instead of practical. The DPD should have taken strategic steps in helping to succeed the interests of the regional community of developemnts.